Patrick [videorecording (DVD)] - Fletcher, Mandie; Fletcher, Mandie; Skrein, Ed, 1983-; Edmondson, Belinda; Saunders, Jennifer (Screen Media Films, 2019)
A young woman inherits her late grandmother's spoiled pug named Patrick.